Effect of Fiber-Telescope Coupling Losses on Wideband Wavelength Division Multiplexing in Free Space Optical Communications - Abdulrahman. Almukhtar; Abdulla Abass; Mudhafer. Ali (Engineering and Technology Journal, 2022)
The effect of telescope losses (TL) on wideband wavelength division multiplexing (Wideband-WDM) based on free-space optical communication (FSOC) is investigated via OptiSystem software. In this work, both single and dual channel FSOC systems are investigated under different communication weathers: clear, haze, rain, and fog with attenuation losses of 0.2 dB/km, 2.3 dB/km, 4.3 dB/km, and 8.0 dB/km, respectively. The TL measures the coupling efficiency between the fiber and telescope in the transceiver assembly; therefore, is considered an important design parameter for the FSOC and hybrid optical communication system. According to the results, the maximum TL is 23 dB and 29 dB for single and dual FSOC, respectively, at the clear weather condition and for 1 km communication distance. This means that the dual-channel system could afford higher losses than the single system by approximately 26.1 %. Furthermore, this ratio is approximately the same for the other weather conditions, 28.6 %, 31.6 %, and 40 % for the hazy, rain, and fog weather, respectively.